ERROR ANALYSIS OF USING PREPOSITION MADE BY STUDENTS IN SHOWING DIRECTION - Sallata, Yizrel Nani (Fakultas Keguruan dan Ilmu Pendidikan, 2014)
In the process of acquiring the language, learners slowly fix the mistakes bounding for gaining more stable skill in speaking the language. Every language learner does realize that being able to speak in that language is the ultimate aim of learning that language. They also realize that in gaining the aim, they have to learn many things including grammar. In Indonesia, teaching English as a foreign language is felt difficult without teaching the students its grammar. The difficulty to learn English without learning grammar appears because it is very difficult to find a total immersion situation where everybody who is involved in speaks English. This research is descriptive which analyzes recording data. The population of this research is the fourth-semester students of English department UKI Toraja which consists of 280 students divided into 8 classes. This research showed most of the errors that the students make are about the use of preposition in. At and of are other prepositions that are inappropriately used.